Paralleled SiC MOSFETs Circuit Breaker With a SiC MPS Diode for Avalanche Voltage Clamping - Taro Takamori; Keiji Wada; Wataru Saito; Shin-ichi Nishizawa (IEEE Open Journal of Power Electronics, 2024)
This paper proposes a solid-state circuit breaker comprising silicon carbide (SiC) MOSFETs and a SiC diode, based on the principle of avalanche voltage clamping. The key challenge in realizing a solid-state circuit breaker lies in reducing conduction loss. A parallel connection of power semiconductor devices is the suitable configuration that can meet these requirements. However, in such a configuration, the current balance during cutoff operation may be affected by the variation in the breakdown voltage characteristics of the power semiconductor devices. To address this issue, the proposed circuit breaker employs clamping with a SiC merged pin Schottky (MPS) diode, with high avalanche tolerance and robust characteristics under repetitive avalanche events. The effectiveness of the proposed solid-state circuit breaker is validated through experiments conducted in an unclamped inductive switching (UIS) test circuit using a 400-V, 50-A DC distribution system. Eventually, the demonstrations indicate that the SiC diode clamping method contributes to more compact implementations for solid-state circuit breakers.